Neural progenitor cells isolated from the subventricular zone present hemichannel activity and form functional gap junctions with glial cells - Talaverón, Rocío; Fernández, Paola; Escamilla, Rosalba; Pastor, Angel M.; Matarredona, Esperanza R.; Sáez, Juan C. (Frontiers in Cellular Neuroscience, 2015)
The postnatal subventricular zone lining the walls of the lateral ventricles contains neural progenitor cells (NPCs) that generate new olfactory bulb interneurons. Communication via gap junctions between cells in the subventricular zone is involved in NPC proliferation and in neuroblast migration towards the olfactory bulb. Subventricular zone NPCs can be expanded in vitro in the form of neurospheres that can be used for transplantation purposes after brain injury. We have previously reported that neurosphere-derived NPCs form heterocellular gap junctions with host glial cells when they are implanted after mechanical injury. To analyze functionality of NPC-glial cell gap junctions we performed dye coupling experiments in co-cultures of subventricular zone NPCs with astrocytes or microglia. Neurosphere-derived cells expressed mRNA for at least the hemichannel/gap junction channel proteins connexin 26 (Cx26), Cx43, Cx45 and pannexin 1. Dye coupling experiments revealed that gap junctional communication occurred among neurosphere cells (incidence of coupling: 100%). Moreover, hemichannel activity was also detected in neurosphere cells as evaluated in time-lapse measurements of ethidium bromide uptake. Heterocellular coupling between NPCs and glial cells was evidenced in co-cultures of neurospheres with astrocytes (incidence of coupling: 91.0 ± 4.7%) or with microglia (incidence of coupling: 71.9 ± 6.7%). Dye coupling in neurospheres and in co-cultures was inhibited by octanol, a gap junction blocker. Altogether, these results suggest the existence of functional hemichannels and gap junction channels in postnatal subventricular zone neurospheres. In addition, they demonstrate that subventricular zone-derived NPCs can establish functional gap junctions with astrocytes or microglia. Therefore, cell-cell communication via gap junctions and hemichannels with host glial cells might subserve a role in the functional integration of NPCs after implantation in the damaged brain.